Made in Spain. Season 2 [videorecording (DVD)] - Ciardiello, Dominick; Swensen, Paul; Andrés, José, 1969- (Distributed by PBS Home Video, 2008)
Jose Andres brings the exciting flavors of his native Spain to the American audience with easy and informative recipes created in his Washington, D.C. kitchen using products found in the U.S..